Uji mikrobiologi dan uji etanol pada minuman sari buah mengkudu di UD X - Wahyu Kanti Dwi; Dian Setiya Widodo (AGROINTEK, 2023)
The noni juice drink is a processed product of UD X located in Lumajang. Many noni producers are found in Lumajang and are dominated by small entrepreneurs. During the production process of noni juice, the aspects of sanitation, hygiene, and ethanol content were not paid attention to. The aims of this study were: to perform microbiological tests related to the presence of Coliform and Salmonella sp bacteria, and to test the ethanol content of noni juice drinks according to SNI. The research design used a completely randomized design and was analyzed using ANOVA. Microbiological test using the MPN (Most Probable Number) method, and the ethanol test method, namely gas chromatography. The results of the study showed that the microbiological test based on BPOM No. 16 of 2016 showed that the E-Coli, Salmonella and staphylococcus test was worth 0, meaning that there were no microbes and bacteria in the drink. Based on the results of the BNT test (P5 %), showed that the treatments were significantly different. That is, the fermentation time dramatically affects the presence of E-Coli and Salmonella in noni juice drinks. Furthermore, according to PerKa No. 14 of 2016, concerning alcoholic beverages. The ethanol content of noni drink is 0.5% - 5%. However, the results of the BNT test (P5 %) showed no significant effect between fermentation time on the ethanol content produced in noni juice drink